A Caritas Arquidiocesana de São Paulo: sua missão como organismo eclesial de promoção humana - Camargo, Carlos Augusto de Oliveira (2015)
The Industrial Revolution gave strength to the liberal capitalist economic system, which caused a strong social asymmetry between rich and poor. This separation is reinforced and maintained by social structures of injustice, based on greed for profit and the idolatry by goods materials. The Catholic Church has the sole mission of evangelization and offer their doctrine to social issues that afflict humanity. Caritas is the entity linked to Arquidiocese de São Paulo with a mission to animate the charitable service. We analyze the ethical Christian principles that guide the work of the Caritas Archdiocese of São Paulo and identify some interpellations of social injustice, from the contemporary context that stimulate effective action of the Church and society. We will see that solidarity and the welcoming gesture will always be needed. The dissertation will be seated in the literature and interviews with some people who are part of the history of the Archdiocesan Caritas